Arrangement of 30S heterogeneous nuclear ribonucleoprotein on polyoma virus late nuclear transcripts. - Steitz, J A (1981)
Heterogeneous nuclear ribonucleic acid (hnRNA) molecules in eucaryotic cell nuclei associate with a well-defined group of abundant, highly conserved proteins to form heterogeneous nuclear ribonucleoproteins (hnRNP). The exact manner in which these 30S complexes assemble on nuclear transcripts, however, has not been well documented. To determine whether any site selectivity in the formation of hnRNP can be detected (e.g., preferential recognition of intervening sequences or of premessage regions), we investigated the distribution of 30S hnRNP on a particular nuclear RNA, the polyoma virus late transcript. Hybridization studies showed not only that the majority of polyoma late nuclear RNA sequences can be isolated in the form of 30S complexes, but that the RNP were located equally on intervening sequences and premessage portions of the transcript. The latter conclusion was confirmed by ribonuclease T1 oligonucleotide fingerprint analysis of polyoma virus-specific RNA recovered from native 30S complexes. However, fingerprint analysis of the small segments of viral RNA in the 30S fraction that survived extensive ribonuclease treatment revealed that oligonucleotides corresponding to intervening sequences were preferentially lost. We discuss these findings in relation to the structure of 30S hnRNP and their function in RNA biogenesis.